Lifting the veils: the mystique (mistake) of Penang legal history - Mobarak Ali, Bashiran Begum; Muhamad, Siti Junaidah; Ramli, Noriah (IIUM Press, 2009)
After the implementation of the Charter of Justice 1807, the Penang Courts believe that in order to provide justice to the natives of the state, the lex loci of Penang should be the English Common law and the rules of the Equity applicable in England. However, there was claimed made by the Sultan of Kedah then that he was merely allowing the British to occupy the island while taking care of the Sultan and His Kingdom against his enemies, especially Siam. So, his allegation was that Penang was never given away to British. To make matter attention-grabbing, in 1800, Seberang Prai was taken by British on the assumption that the Sultan and His Kingdom will be protected. In 1829, the Courts took a turn by claiming that they had never heard of Sultan of Kedah but no authority to deal with the land as sovereignty actually belonged to Siam! There is a great deal of legal historical discrepancies that surrounds the British occupation of Penang. Therefore,it is the intention of the writers to trace, clarify and analyse the legal history on the acquisition of Penang and the state of affairs of Kedah and to confirm that Islamic law was the lex loci of both, Kedah and Penang.